Administração da lecitina artinm em camundongos favorece o controle parasitário durante a infecção aguda pelo trypanosoma cruzi - MIGUEL, Camila Botelho (2012)
Background: Chagas disease, also known as American trypanosomiasis, is caused by an anthropozoonozie infection of the protozoan Trypanosoma cruzi (T. cruzi), which is a major medical-social problem in Brazil and a serious public health problem in Latin America. Currently, the treatment is performed by chemotherapeutic agents and medications benznidazole and nifurtimox. Lectins are proteins or glycoproteins of sugar binder, which agglutinate cells and or precipitate glycoconjugates. The lectin ArtinM important property is endowed with immunomodulating by exerted by induction of IL-12. Objectives: Evaluate the effect of immunomodulation by ArtinM promoted during the acute phase of experimental infection with T.cruzi. Methods: Were used forty male mice of lineage BALB/c with ten week old, divided in the groups: Control treated with Saline, Control treated with Lectin, Infected treated with Saline e Infected treated with Lectin. The infection with the T.cruzi was performed with an inoculum of 3x103 blood trypomastigotes of the “Colombiana” strain. Animals from the groups Control treated with Saline and animals Infected treated with Saline received 100μL of saline 0,9% and the groups Control treated with Lectin and Infected treated with Lectin received 0,5μg/100μL of Lectin ArtinM. Saline and Lectin of administration was performed for three consecutive days prior to infection and the in the fifth, tenth and fifteenth days after infection. The parasitemia was performed on the seventh, fourteenth and twenty-first day after infection. After 23 days of infection the animals were euthanized and necropsied. Blood was collected for analysis of hemogram and count of reticulocytes. The plasma, spleen and atria performed the quantification of IL-12 p40, IL-10, IFN-γ and TNF by ELISA; ventricles for histological analysis, which were performed with 6μm thick sections and strained with hematoxylin and eosin. We analyzed the percentage of the area of inflammatory infiltrate through the grid points with predetermined area and the number of nests of T.cruzi by immunohistochemistry. Values were considered significant when p<0.05. Results: The group Infected treated with Lectin showed lower numbers of parasites, a significant difference in the fourteenth and twenty-first day of infection. In the analysis of hemogram, we found a decrease in erythrocyte values stemming from the infected groups, including number of red blood cells, hemoglobin, hematocrit, hematimetrics indices (MCV and MCH) and Amplitude distribution of red blood cells (RDW), besides the increase in reticulocytes. No differences in platelet count. Increase in total leukocytes and therefore neutrophils, lymphocytes and monocytes. In histological analysis, there was a reduction in the percentage of the area of inflammatory infiltrate and nests of T. cruzi in heart tissue. In the cytokines evaluation of the measurement profiles of the different organs were similar reduction of IL-12 p40, TNF and IFN-γ and IL-10 increased in the group Infected treated with Lectin ArtinM in comparasion with group Infected treated saline. Conclusion: We conclude that the lectin ArtinM has a biological effect in Balb/C during the acute phase of experimental infection with T.cruzi.